A rebbachisaurid-mimicking titanosaur and evidence of a Late Cretaceous faunal disturbance event in South-West Gondwana - Filippi, Leonardo Sebastián (2024)
The evolution of ecosystems during the late Mesozoic on the southern landmasses is complex and still poorly known. Starting from a single vicariant LaurasianeGondwanan scenario, the paleobiogeographic and biostratigraphic models have become more complex, including vicariant, dispersal, and local extinctions as major drivers of changes in the Cretaceous ecosystems during the isolation and posterior fragmentation of Gondwana. However, the direct effects of replacement and the adaptive evolution of terrestrial vertebrates to fill vacant ecological niches after disruptive ecological events have been poorly discussed. Here, we provide a preliminary description of a nearly complete new titanosaurian sauropod from the Upper Cretaceous of Patagonia, Inawentu oslatus gen. et. sp. nov., that shows remarkable convergent anatomical traits with rebbachisaurid sauropods. A phylogenetic analysis recovers it within a not previously recovered titanosaurian subclade, named Clade A, which would be endemic to the Upper Cretaceous of South America. The convergent evolution between rebbachisaurids and Clade A members is interpreted as the result of the same ecological niche exploitation. The biostratigraphic scenario during the Late Cretaceous of South America leads to interpret rapid speciation of the titanosaurs because of filling the empty ecological niche left by the extinction of the rebbachisaurids, an idea concordant with a regional disturbance event of the ecosystems in this continent between 90 and 85 Ma.